JURIDICAL ANALYSIS OF THE IMPACT OF GOODS STANDARDISATION ON MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN ECONOMIC PERSPECTIVE - Yusuf Gunawan (Adisam Publisher, 2025)
This research analyses the juridical impact of the implementation of goods standardisation on Micro, Small and Medium Enterprises (MSMEs) from an economic perspective in Indonesia. Through a normative juridical approach, this research examines key regulations such as Law No. 20 of 2014 on Standardisation and Conformity Assessment and Government Regulation No. 7 of 2021 on the Facilitation, Protection, and Empowerment of MSMEs, which require the fulfilment of product standard certificates for businesses. The results show that standardisation provides benefits in the form of increased competitiveness, product quality assurance, and expanded market access, but also poses challenges in the form of certification cost burdens, complexity of procedures, and limited resources for micro-scale MSMEs. Government policies through certification facilitation, incentives, and simplification of procedures are considered important to ensure legal protection for consumers while encouraging the sustainability of MSME businesses. Thus, the optimisation of an inclusive and equitable standardisation policy is key in strengthening the position of MSMEs as a pillar of the national economy in the era of global competition.